Mechanism of Liquefaction-Induced Large Settlements of Buildings - Zaheer Ahmed Almani (Mehran University Research Journal of Engineering and Technology, 2012)
In this paper, mechanism of liquefaction-related large settlements of the soil-structure system during the earthquake was studied using numerical modelling. The isolated shallow strip plane strain footing pad, supporting a typical simple frame structure, was founded on the ground at the shallow depth from the level ground surface. This system was modelled as plane-strain using the FLAC (Fast Lagrangian Analysis of continua) 2D dynamic modelling and analysis code. This case focuses on the basic mechanisms of liquefaction-induced large deformations of the structure during an earthquake and will provide a benchmark model case for comparison with the model case in which jet grouted columns are provided as ground reinforcement. The results showed that large settlements of shallow foundations in punching shear are triggered during cyclic excitation. These large settlements under the structure are driven by load of structure and earthquake excitation. Monotonic shear deformation, lateral shear deformations and volume change of soil are main phenomena under the structure when the pore pressure rises and soil is liquefied in cyclic loading.